Chinese Stroke Association guidelines for clinical management of cerebrovascular disorders: executive summary and 2019 update of clinical management of cerebral venous sinus thrombosis. Issue 2 (13th May 2020) - Fan, Yuhua; Yu, Jian; Chen, Hongbing; Zhang, Jian; Duan, Jiangang; Mo, Dapeng; Zhu, Wenhao; Wang, Bo; Ouyang, Fubing; Chen, Yicong; Lan, Linfang; Zeng, Jinsheng
Abstract : Aim: Cerebral venous sinus thrombosis (CVST) is a less common cerebrovascular disease that predominantly affects young patients. The incidence of CVST is 2–5/10 000 000/year, accounting for 0.5%–1% of all stroke. To reduce mortality and morbidity associated with CVST, Chinese Stroke Association commissioned the authors to write the current guideline on the management of CVST. Methods: PubMed (MEDLINE), CNKI and Wanfang database were searched for studies related to CVST from 1 January 1990 to 31 July 2019. Data were synthesised by evidence tables. Each recommendation was fully discussed by the writing group members and reviewed by Chinese Stroke Association Stroke Fellow Committees. Levels of evidence grading algorithm of Chinese Stroke Association was used to grade each recommendation. Results: This guideline mainly focuses on the diagnostic evaluation, therapeutic strategies and secondary prevention of CVST. CT/CTV and MRI/MRV are recommended in the initial imaging evaluation of patients with suspected CVST. Anticoagulation therapy with low-molecular weight heparin should be initiated in patients with CVST immediately. After the acute stage, warfarin is recommended for 3–6 months to prevent the recurrence of CVST and other venous thromboembolic events. Conclusions: The guideline summarises the current evidence regarding the management of CVST, and provides references for diagnosis, treatment and secondary prevention of CVST in China.